Communities, Landscapes, and Interaction in Neolithic Greece. - Sarris, Apostolos (International Monographs in Prehistory: Archaeological Ser., 2018)
The last three decades have witnessed a period of growing archaeological activity in Greece that have enhanced our awareness of the diversity and variability of ancient communities. New sites offer rich datasets from many aspects of material culture that challenge traditional perceptions and suggest complex interpretations of the past. This volume provides a synthetic overview of recent developments in the study of Neolithic Greece and reconsiders the dynamics of human-environment interactions while recording the growing diversity in layers of social organization. It fills an essential lacuna in contemporary literature and enhances our understanding of the Neolithic communities in the Greek Peninsula.